BIOMEDJ 2019
DOI: 10.32392/biomed.63.3
|View full text |Cite
|
Sign up to set email alerts
|

MYCN overexpression is linked to significant differences in nuclear DNA organization in neuroblastoma

Abstract: Rangel-Pozzo et al. (2019) MYCN overexpression is linked to significant differences in nuclear DNA organization in neuroblastoma. SPG BioMed 1(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This result aligned with our telomere data, which showed more telomere signals and probably more chromosomes. Previous studies have shown that the number of DNA-poor spaces increases in tumor cells [ 12 , 20 , 21 , 22 ], suggesting chromatin remodeling. However, these DNA-free interchromatin areas could be nucleoli, which display the same morphology as DNA-poor spaces and could also be associated with the absence of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This result aligned with our telomere data, which showed more telomere signals and probably more chromosomes. Previous studies have shown that the number of DNA-poor spaces increases in tumor cells [ 12 , 20 , 21 , 22 ], suggesting chromatin remodeling. However, these DNA-free interchromatin areas could be nucleoli, which display the same morphology as DNA-poor spaces and could also be associated with the absence of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the CRISPR p53 deleted cells show more DNA-free/poor spaces than their normal counterparts (indicated with circles), a characteristic of tumor cells [58][59][60]. From the 3D-SIM images, the different length-scales of DNA organization can be interpreted as granules with different diameters, and the cumulative size distribution of DNA structures can be represented as a curve showing the distribution of different granule sizes in that particular cell [58][59][60]. Histograms for the structure of DNA and structure of DNA-poor spaces for MCF-7 (wt and CRISPR-p53) and normal breast cell lines are shown in Figure 1B.…”
Section: Analysis Of Dna Sstructure Reveals Differences In Dna Structmentioning
confidence: 99%
“…3D-SIM can offer the ability to capture resolutions up to 100 nm resolution in the xand yaxes and 200-250 nm in the z-axis, which can reveal structural information much closer to the scale of higher order DNA structures within the nucleus [56,57]. This technique has previously been used to quantify broad scale changes in DNA ultrastructure that occur after malignant transformation in cancers [58][59][60]. 3D-SIM technology can be used to capture the size and intensity of fluorescent DNA signals in three dimensions in nuclei stained with DAPI (4 ,6 diamidino-2-phenylindole), revealing the size distribution of DNA structures and DNA-poor spaces in super-resolution imaging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations